ترجمة المضمون التربوي في أدب الأطفال: الخرافة نمودجا: Translating educational content in children’s literature: case of fable - ternifi, Khadidja alla; Grin , Zhour (Maalim, 2023)
This study aims to identify the translational strategies and techniques adopted in translating children's literature, especially fables or stories anthropomorphized by animals that are intended for children, and how the translator deals with its educational contents. The present paper relies on the analytical-educational approach, where a sample of the educational values ​​included in the approved translations of La Fontaine's fable is analyzed. As the translation of the educational content in the fable is not an easy matter, as education includes different types of cognitive, social, moral and other values, during the transfer into the Arabic language which requires great linguistic skill and special artistic ability in order to entertain the child, but educate and guide him at the same time. Also, adaptation in the transfer of children’s literature, is generally a strategy in free translation represented in the translator looking first and foremost at what suits the recipient in the target language by deleting, adding, submitting and delaying, so that both artistic and educational images are manifested alike.